Education in Urban Health: the experience of Public Health residents in an Italian high school: Chiara Cadeddu. (25th October 2022) - Cadeddu, C; Zjalic, D; Lanza, TE; Nachira, L; Perilli, A; Paladini, A; Lombardi, GS; Di Russo, M; Ricciardi, W; Damiani, G
Abstract: Background: Urban health has become an increasingly important aspect of Public Health curriculum for residents as people living in urban areas will substantially rise in the next 30 years so will their impact on health. Residents are both contributors and partners in creating sustainable solutions for their growing cities and can be involved in this aim as individual learners and also educators for younger students. Objectives: A group of 15 Italian residents in Public Health were involved in creating and delivering 4 lessons on urban health to 319 students at Nomentano High School in Rome during spring 2022. After the 4th lesson, semi-structured interviews were conducted with the residents in order to assess perceptions, acceptance, barriers and facilitators of the experience. Data was gathered anonymously and analyzed using standard qualitative methods. Results: All the residents answered the interview. Almost all reported the experience as highly impactful for training, team building, and increase in accountability. Most of residents also felt more confident on the topic of urban health and more involved in concrete actions for tackling pollution and climate change after delivering the lessons. Most perceived barriers mentioned were difficulties interacting with students, especially during the first two lessons, and their compliance. The opportunity to give lessons in the high school setting facilitated direct contact with students and better feedback was received. Conclusions: Giving responsibility and leadership roles to Public Health residents and involving them in the education of younger students could improve their self-confidence and feelings of value and helpfulness, especially for urban health and climate change issues sensed by youth. Further experiences in other settings, specialties, and countries could be valuable to notice differences related to age groups and personal involvement. Key messages: The involvement of Public Health residents in education on urban health is highly impactful and well perceived for their personal growth. This kind of experience is applicable to other relevant topics in Public Health.